An Analysis of Therapeutic Communication and Student Burnout at Maahad Tahfiz Akademi Miftahul Ulum Ampang Selangor Malaysia - Siti Mariyam; Sri Rizqi Wahyuningrum; Iswatun Hasanah; Anna Aisa; Ayu Raudhatul Jannah; Saadiyah Binti Harun (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
Qur’an memorization (tahfiz) involves ongoing cognitive and emotional processes that may contribute to psychological stress among students. In this context, the quality of communication between teachers and students plays a crucial role in maintaining psychological balance during the learning process. This study aims to analyze the therapeutic communication practices of tahfiz teachers and examine their effect on student burnout at Maahad Tahfiz Akademi Miftahul Ulum Ampang, Selangor, Malaysia. This study employed a mixed-methods approach with an explanatory design. Quantitative data were collected through a Likert-scale questionnaire administered to 28 students and analyzed using simple linear regression. Meanwhile, qualitative data were obtained through interviews and observations to enrich the quantitative findings. The results indicate that therapeutic communication among tahfiz teachers falls within the moderate-to-high category, particularly in the dimensions of empathy and warmth. Student burnout was found to be at a moderate level, with a tendency toward increased exhaustion. Regression analysis revealed a significant negative relationship between therapeutic communication and student burnout, with an explanatory contribution of 40.1%. Thus, therapeutic communication serves as a protective factor against student burnout and contributes to both the effectiveness of tahfiz learning and students’ mental well-being.